PERBANDINGAN METODE PETA KONSEP DAN BAGAN DIKOTOMI KONSEP (BDK) TERHADAP HASIL BELAJAR PESERTA DIDIK MATERI KEANEKARAGAMAN HAYATI KELAS X SMA/MA - Ruqoyyah Ruqoyyah; Delima Engga Maretha; Dini Afriansyah (Bioilmi: Jurnal Pendidikan, 2021)
The purpose of this study was to determine an effective method between the concept map and the concept dichotomy chart (BDK) of biodiversity on student learning outcomes. The methodology used is Quasi experimental design using the design of The Group Pretest-Posttest Design. The data collection techniques used were interviews, tests and documentation. Quantitative data analysis used SPSS Version 22. The results showed that there was a significant difference between before and after treatment with the Concept Map and Concept Dichotomy Chart (CDC) with an average Concept Map of 71,07 and CDC 94,28. All categories showed a significant increase after treatment. In this study it is said that the Sig. (2 tailed) is less than 0.05 (0.000 <0.05) then Ha is accepted and H0 is rejected. So it is concluded that the learning outcomes of Biology taught using the Concept Map and Concept Dichotomy Chart (CDC) learning method on biodiversity material can be used to improve learning outcomes, especially students' mastery of concepts.